Re-emergence of Crimean-Congo hemorrhagic fever virus in Central Africa. - Gilda Grard; Jan Felix Drexler; Joseph Fair; Jean-Jacques Muyembe; Nathan D Wolfe; Christian Drosten; Eric M Leroy (Public Library of Science (PLoS), 2011)
Crimean-Congo hemorrhagic fever (CCHF) is a severe tick-borne disease well recognized through Europe and Asia where diagnostic tests and medical surveillance are available. However, it is largely neglected in Africa, especially in the tropical rainforest of Central Africa where only sporadic human cases have been reported and date back to more than 30 years. We describe here an isolated human case that occurred in the Democratic Republic of the Congo in 2008 and performed phylogenetic analysis to investigate whether it resulted from a regional re-emergence or from the introduction of a novel virus in the area.Near complete segment S and partial segment M sequences were characterized. Bayesian phylogenetic analysis and datation were performed to investigate the relationship between this new strain and viral strains from Africa, Europe and Asia. The new strain is phylogenetically close to the previously described regional genotype (II) that appears to be specific to Central Africa. Phylogenetic discrepancy between segment S and M suggested genetic exchange among local sublineages, which was dated back to 130-590 years before present.The phylogenetic analyses presented here suggest ongoing CCHF virus circulation in Central Africa for a long time despite the absence of reported human cases. Many infections have most probably been overlooked, due to the weakness of healthcare structures and the absence of available diagnostic procedure. However, despite the lack of accurate ecological data, the sporadic reporting of human cases could also be partly associated with a specific sylvatic cycle in Central Africa where deforestation may raise the risks of re-emergence. For these reasons, together with the high risk of nosocomial transmission, public health authorities' attention should be drawn to this etiological agent.